Development and Validation of a Tobacco Testing Laboratories Assessment Tool - Goel, Sonu; Goel, Chirag; Walia, Diksha; Sunthlia, Avinash; Swasticharan, Leimapokpam; Joshi, Rajendra P.; Goel, Atul (PLOS ONE, 2025)
Background Effective regulation and control of tobacco products require robust laboratory testing capabilities to ensure quality, safety and compliance with relevant standards. Currently, no standardized assessment tool exists globally to evaluate the tobacco testing laboratories. This study aims to address this gap by developing the Tobacco Testing Laboratory Assessment Tool (TTLAT). This tool aligns with the WHO-FCTC on Tobacco Control’s Article 9, which calls for the adoption and implementation of effective testing, measuring, and regulation measures. Methodology The TTLAT was developed through a systematic literature review and a two-round Delphi technique involving 24 experts. The tool was then validated in four National Tobacco Testing Laboratories in India. Content validity was assessed using the Item-Content Validity Index (I-CVI) and Scale-Content Validity Index (S-CVI). Construct validity was evaluated through exploratory and confirmatory factor analyses. Internal consistency reliability was measured using Cronbach’s alpha. Results The final TTLAT comprises 213 items across 11 critical domains including General Information (17), Documents (37), Organization and Management (10), Human Resources (28), Infrastructure (7), Equipment (23), Consumables and Reagents (10), Sample Handling (17), Tobacco Product Analytes (8), Data Management (36), and Biosafety and Biosecurity (20). Content validity analysis showed excellent results. Exploratory factor analysis identified six factors accounting for 52.5% of the total variance. Confirmatory factor analysis demonstrated good model fit (CFI = 0.91; TLI = 0.90; RMSEA = 0.05; SRMR = 0.06). The tool showed high internal consistency reliability across factors (Cronbach’s alpha 0.72–0.92). Conclusion The TTLAT demonstrates strong psychometric properties and provides a comprehensive, standardised approach for assessing tobacco testing laboratory capacity.